ANXC7 Is a Mitochondrion-Localized Annexin Involved in Controlling Conidium Development and Oxidative Resistance in the Thermophilic Fungus Thermomyces lanuginosus - Xie, Xiang-Li; Yang, Huan; Chen, Li-Na; Wei, Yi; Zhang, Shi-Hong (Frontiers in Microbiology, 2018)
Annexins (ANXs) are widely expressed and structurally related proteins that play multiple biological roles across animals, plants, and fungi. Although ANXs have been localized to the cytosol and the cell membrane and the molecular basis of the four annexin repeats is well established, the in vivo roles of these proteins are still far from clear, particularly in regard to filamentous fungi. Thermomyces lanuginosus, a thermophilic fungus, is widely used in the fermentation industry; however, the role of ANX in this organism is unknown. In this study, a single ANX homologue (ANXC7) was identified and characterized in T. lanuginosus. The expression pattern indicated that ANXC7 is closely associated to conidium development, and it accumulated in the mitochondria of the forming conidia. The deletion of ANXC7 (∆ANXC7) resulted in no obvious phenotype related to colony growth on solid CM medium. However, when ∆ANXC7 was grown in CM liquid culture, the mycelium masses appeared to be larger and looser compared to wild type. Additionally, the dry weight of the mutant mycelia was significantly increased. Under conditions that compromise cell wall integrity, ∆ANXC7 was less vulnerable than wild type in regard to such damage. Moreover, based on a surface hydrophobicity test, the ∆ANXC7 strain was clearly less hydrophobic. The growth of ∆ANXC7 was inhibited when grown under selected stress conditions, particularly in regard to salt stress; however, the oxidative resistance to exogenous H2O2 in ∆ANXC7 was increased, and endogenous H2O2 levels within the ∆ANXC7 were lower than in wild type, suggesting ANXC7 specifically controls oxidative resistance. Based on microscopic observation, 4-day-conidia were more prevalent than 5-day conidia on the conidiophore stalk of ∆ANXC7, even thought ∆ANXC7 demonstrated an increased production of conidia during these days, indicating precocious conidial maturation and shedding from the conidiophore stalk in this strain. Taken together, our data indicate that ANXC7 localizes to the mitochondria and is involved in controlling conidium development and oxidative resistance in T. lanuginosus.